Pertumbuhan dan Pemeliharaan Tanaman Gaharu (Aquilaria malaccensis) di Persemaian Permanen UPTD Balai Sertifikasi dan Perbenihan Tanaman Hutan Dinas Kehutanan Sumatera Barat - Aura Evrisantya; Violita Violita; Mika Lestaria (Lembaga Yasin AlSys, 2026)
Agarwood (Aquilaria malaccensis) is one of the non-timber forest products with high economic value because it produces aromatic resin used in the perfume, cosmetics, traditional medicine, and aromatherapy industries. This internship activity aimed to study and describe the early growth and maintenance of agarwood seedlings at the Permanent Nursery of the UPTD Balai Sertifikasi dan Perbenihan Tanaman Hutan (BSPTH) Dinas Kehutanan Sumatera Barat as part of efforts to support the cultivation and conservation of agarwood plants. The activity was carried out from January to February 2026 using a descriptive method through direct observation of the seedling growth and maintenance process. The observations showed that the agarwood seeds used had good quality with high viability. Optimal seedling growth was supported by regular watering, the use of shade, loose planting media, and periodic weed and pest control. The conclusion of this activity affirms that the maintenance of agarwood seedlings in nurseries plays an important role in producing quality seedlings, supporting successful cultivation, and promoting the conservation and sustainable management of forest resources. The implications of this activity indicate the need to apply regular and adaptive nursery maintenance techniques so that the early growth of agarwood seedlings can proceed optimally.